2016
DOI: 10.22302/ppbbi.jur.mp.v80i2.39
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas antibakteri ekstrak kulit buah kakao (Theobroma cacao L.) terhadap Escherichia coli, Bacillus subtilis, dan Staphylococcus aureus

Abstract: Aktivitas antibakteri ekstrak kulit buah kakao (Theobroma cacao L.) terhadap Escherichia coli, Bacillus subtilis, dan Staphylococcus aureus Antibacterial activity of cocoa pod husk extract (Theobroma cacao L.) against Escherichia coli, Bacillus subtilis, and Staphylococcus aureus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Other research has shown that the potential of cacao pod extract to inhibit bacterial growth in the urinary tract and that the higher the extract concentration, the larger the inhibition zone against bacterial growth. The largest inhibition zone of Staphylococcus aureus and Escherichia coli growth was formed at a 64% concentration, and the result was 10 mm and 8.83 mm, respectively (Mulyatni et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other research has shown that the potential of cacao pod extract to inhibit bacterial growth in the urinary tract and that the higher the extract concentration, the larger the inhibition zone against bacterial growth. The largest inhibition zone of Staphylococcus aureus and Escherichia coli growth was formed at a 64% concentration, and the result was 10 mm and 8.83 mm, respectively (Mulyatni et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…The antimicrobial compound in cacao pods is flavonoid. The flavonoids in cacao pods are catechin, anthocyanin and leukoanthocyanidine (Mulyatni et al, 2012). Flavonoids are phenolic compounds and the result of phenylpropanoid cycle synthesis as a response against microbial infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids 3.91% bind to proteins via hydrogen bonds so that the protein structure becomes damaged and disrupts the permeability of cell membranes resulting in bacterial death 8 . Terpenoids of 2.94% work by binding to porin (transmembrane protein) on the outer membrane of the cell wall bacteria that can create instability from bacterial cell membrane permeability, causing an imbalance of ions and bacterial cell wall metabolites causing nutrient deficiencies and the occurrence of cell necrosis and apoptosis which can cause death from bacterial cells 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry the use of herbal alternatives has been used for hundreds of years and has long been known for its high antibacterial ability, analgesic, biocompatibility, anti-inflammatory and anti-oxidant. 7 Indonesia is the third largest cocoa producer in the world, based on data from the Directorate General of Plantation, the total Indonesian cocoa production in 2010 was 900 thousand tons 8 . Cocoa pods contain alkaloids, flavonoids, tannins, saponins and terpenoids 9 .…”
Section: Introductionmentioning
confidence: 99%